Comparison of the pressure time product during synchronous intermittent mandatory ventilation and continuous positive airway pressure. Issue 3 (1st September 2000) - Manczur, T; Greenough, A; Rafferty, G F
Abstract : OBJECTIVE: To compare the effect of continuous positive airway pressure (CPAP) with synchronous intermittent mandatory ventilation (SIMV) during weaning, by measurement of the pressure time product (PTP). The PTP is an estimate of the metabolic work or oxygen consumption of the respiratory muscles. PATIENTS: Forty children, median age 14 months (range 1 month to 17 years) were studied immediately prior to extubation. METHODS: The PTP, derived from airway pressure changes, was measured while the child received SIMV (with or without pressure support) and then CPAP. A pneumotachograph was placed between the endotracheal tube and ventilator circuit. Its flow signal was used to indicate the beginning and end of inspiration. Airway pressure was measured from the pneumotachograph and the area subtended by the pressure curve (PTP) calculated using a modified Labview programme. RESULTS: The median PTP was significantly lower on SIMV (17.1 cm H2 O/sec/min, range 0.4 to 60.5) compared to on CPAP (32.6 cm H2 O/sec/min, range 0.1 to 116.7), p < 0.001. CONCLUSION: These results suggest SIMV, rather than CPAP, may be the more efficacious weaning mode in children, and that the time spent on CPAP during weaning should be minimised.